Improvement of Peat Using Portland Cement and Electrokinetic Injection Technique - Moayedi, H.; Kassim, K.A.; Kazemian, Sina; Raftari, M.; Mokhberi, M. (SPRINGER HEIDELBERG, 2014)
Peat is often referred as problematic soil due to its high compressibility, low shear strength, and high water content. However, high surface electrical charge and high cationic exchange capacity of peat makes it a good source for transporting and/or exchange with cations. In this study, a series of batch test is performed to find out the effect of strength improvement of portland cement mixed with the peat. Then, the feasibility of injecting cement electrokinetically into peaty soil environment has been assessed. The microstructure of the treated peat was also investigated by scanning electron microscopy and energy-dispersive X-ray spectrometer analysis. The results showed that the undrained shear strength, pH, and water content of treated peat are affected after electrokinetic treatment. Because of the electrokinetic process, the undrained shear strength was improved to maximum of 308 % and minimum of 30 % in the normalized distance of 0.1 and 0.9 from anode, respectively. The pH was also increased to the maximum of 8 in the normalized distance of 0.1 and 0.9 from the anode. However, the water content was reduced after 7 days of electrokinetic processing.